Mining the social web, Google+ : learn to mine data from a unique social network built around interest-based communities - Klassen, Mikhail; Safari eBooks ([Place of publication not identified] : O'Reilly, 2017)
"Google+ is a social media platform that allows its users to create profile pages and submit posts to interest-based communities. It's become a useful platform for data mining because it organizes user posts according to topic, making it possible to obtain a lot of sample data on any given subject. This course, based on the book "Mining the Social Web" (O'Reilly Media) by Matthew Russell, teaches you how to mine Google+. You'll learn how to access Google+, download public posts, extract and parse text, and analyze the similarity of documents using natural language processing (NLP) techniques and the Python Natural Language Toolkit (NLTK). Learners should have a Google account and a basic understanding of Python."--Resource description page.
Presenter, Mikhail Klassen.
Title from title screen (viewed October 5, 2017).
Date of publication from resource description page.
Keywords: Google+ (Electronic resource); Python (Computer program language); Data mining; Natural language processing (Computer science); Application program interfaces (Computer software); Online social networks; Electronic books